Pengukuran Kekuatan Bending Material Komposit dari Limbah Ampas dan Sekam Kopi - Nurmalia, Nurmalia; Hartono, Medelyn Angel; Ary Noviyanti, Anastasia (Jurnal Otomasi Kontrol dan Instrumentasi, 2023)
Growing coffee consumption in Indonesia has resulted in increasing used coffee ground and husk containing tannins, alkaloids, and polyphenols, which oftentime just being dumped in the landfill, causing pollution to the environment. This study aimed to convert coffee waste into composite that can be used to create a valuable product. The coffee waste was used as the dispersed phase and other additional materials as the matrix phase of the composite. Depending on its application, a functional product is subjected to mechanical loads, such as tensile, compressive, torsional, or bending loads. Therefore, it is important to determine the maximum load that can be sustained by the material before it breaks, commonly referred to as material strength. Various mixture of coffee waste and matrix phase were explored, and the bending strength of resulted composites were measured using  Universal Testing Machine (UTM). To maximize the utilization of coffee waste, the best composite with optimal bending strength and the highest volume ratio of coffee waste to matrix component was investigated. It was found that the best composite consisted of a mixture of epoxy resin and white cement as the matrix with a coffee waste: matrix ratio of 50:50 and bending strength of 29.63 MPa.